Restrictive versus liberal oxygenation targets in patients with acute heart failure and pulmonary congestion–A protocol for a Randomized Controlled Trial (The REDOX-AHF trial) - Ida Arentz Taraldsen; Anne Sophie Overgaard Olesen; Jasmin Dam Lukoschewitz; Ejvind Frausing Hansen; Olav Wendelboe Nielsen; Christian Hassager; Jens Jakob Thune; Maryam Noory; Arzu Karamat; Jens Dahlgaard Hove; Johannes Grand (PLoS ONE, 2026)
Introduction Acute heart failure (AHF) is the cause of one in twenty hospital admissions. Supplemental oxygen therapy is a routine treatment in the management of patients with dyspnea, including those with AHF. Current guidelines recommend oxygen therapy as part of the initial treatment, if peripheral oxygen saturation (SpO 2 ) is < 90% or partial pressure of arterial oxygen (PaO 2 ) is < 60 mmHg to correct hypoxemia. There is no clear evidence favoring restrictive or liberal oxygenation strategies in patients with acute heart failure. The aim of this study is to compare restrictive and liberal oxygenation strategies in patients hospitalized for acute heart failure. Methods The study is an investigator-initiated, multicenter, prospective, double-blinded, randomized clinical trial. Patients are randomized in a 1:1 fashion to receive one of the two treatment-strategies: liberal oxygenation (SpO 2 target of 96%) or restrictive oxygenation (SpO 2 target of 90%). The intervention is administrated double-blinded using an automated oxygen administration device, titrating the oxygen supplementation towards the intended target SpO 2 without it being visible for patients, investigators or clinical staff. The primary outcome is pulmonary congestion, measured by remote dielectric sensing (ReDS) after 24 hours, adjusted for baseline measurements. Conclusion This study will explore the current uncertainty regarding restrictive and liberal oxygenation targets in acute heart failure.